KEMAMPUAN MENULIS TEKS EKSPOSISI SISWA KELAS X SMA PLUS BINA BANGSA PEKANBARU - Intan Kemuning; Auzar '; Abdul Razak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research investigates the ability of the first year students of SMA Plus Bina Bangsa Pekanbaru in writing exposition texts. The objectivies of this research was to know and describe the ability of the first year students of SMA Plus Bina Bangsa Pekanbaru in writing exposition texts. This research is descriptive-quantitative research. The data of this research was the result of the test in the ability of the first year students of SMA Plus Bina Bangsa in writing exposition texts. The instruments of this research was written test in essay form that has three provisions questions concerning the ability of the first year students of SMA Plus Bina Bangsa Pekanbaru in writing exposition texts. The data collection used test technique. The population of this research was 58 students and 42 students as the sample. The data analysis was descriptive-quantitative method through Kruskall Wallis test. The validity of the data obtained validaton method and examination of answers based on time triangulation. The result of this research seen from result test of the ability of the first year students of SMA Plus Bina Bangsa Pekanbaru in writing Exposition texts. Based on the ability of the first year students of SMA Plus Bina Bangsa Pekanbaru in writing exposition texts included the low category that the mean score was 58,6667.Key Words : Ability, Writing, Exposition Texts.